An integrated approach to formulate a value-based software process tailoring framework - Zakaria, Noor Azura; Ibrahim, Suhaimi; Mahrin, Mohd Nazri (Penerbit UTM Press, 2016)
Software process tailoring is an approach to customise the existing software development process or model that able to meet the software project’s needs. Software development project is unique and identical from one and another whereby the practices and decision should not be equally treated. Software process tailoring requires knowledge and intuition to make decision such as factors involved in the software project, selection of the suitable software process elements and tailoring operations. Software process tailoring practices focusing more on project characteristics factors and employs ad hoc approach in making the decision. In the absent of value-based factors and systematic method in software process tailoring, subjectivity is embedded in decision making process and the software development project suffers from satisfying the stakeholder. This study presents an integrated approach to formulate a Value-Based Software Process Tailoring Framework (VBSPTF) to overcome this problem. The framework is a combination of value-based factors, MoSCoW rules, Quality Functional Deployment (QFD), Activity-Based Costing (ABC), Priority Map, Value Index and Value Graph. This study perhaps can contribute to the software process tailoring practitioners to be exposed with a systematic method to conduct software process tailoring as well as improving the practices and reducing subjectivity in decision making.